O investimento direto estrangeiro como poupança externa para a infraestrutura: um estudo sobre a economia brasileira dos anos 2000 - Oliveira, Alexandre da Silva de (2011)
ABSTRACTThe research analyzes the Brazilian infrastructure, emphasizing the foreign savings impacts, represented by foreign direct investment (FDI), domestic public and private investments, and regulatory and institutional environment of the 2000s. The research focuses an evaluation of the hypothesis that the Brazilian infrastructure development, characterized by natural monopoly, and the state such as an inducer and regulator of long-term economic growth. The rationale is that public investment mainly from Economic Plan such as Plano de Metas and II PND, increased private national and foreign investments until the 1970s. In contrast, the infrastructure bottleneck due to state intervention lack and economic restructuring of 1980-1990s provided an opportunity for the new cycle of infrastructure investments since 2000s, boosted by the macroeconomic fundamentals consolidation with Plano Real and Brazilian Economic Growth Acceleration (PAC). However, there is an unfavorable environment for domestic and foreign private investment in infrastructure because of Brazilian regulatory uncertainties and low level of public investments. Chapter 1 presents a Keynesian and neoclassical theory review on the investment and savings for a closed economy, but also the growth with foreign savings issue as a development strategy for an open economy, such as in Brazil, followed by FDI review. Besides presents the institutions and regulation impacts on investments and, finally, presents the economic planning and the state role as an economic growth long term promoter. Chapter 2 presents the Infrastructure investments cycles, especially for 1930-1970s, industrialization and Infrastructure investments increasing; 1980-1990s State crisis, macroeconomic imbalances, low infrastructure s investments level and privatization redefining the foreign investment role and; 2000s with the review concerning State as the main economic growth inducer and regulator, the new infrastructure s investments cycle due public funding, focusing the BNDES role. Chapter 3 presents the relationship between the Brazilian and foreign capital infrastructure, with emphasizing on FDI inflows/instocks for Brazil and an international comparison with the other BRIC countries